HPV molecular detection from urine versus cervical samples: an alternative for HPV screening in indigenous populations - Torres-Rojas, Francisco I.; Mendoza-Catalán, Miguel A.; Alarcón-Romero, Luz del C.; Parra-Rojas, Isela; Paredes-Solís, Sergio; Leyva-Vázquez, Marco A.; Cortes-Arciniega, Jair E.; Bracamontes-Benítez, Carlos J.; Illades-Aguiar, Berenice (PeerJ, 2021)
Background Cervical cancer (CC) is the fourth leading cause of death from neoplasms in women and is caused by the human papilloma virus (HPV). Several methods have been developed for the screening of cervical lesions and HPV; however, some socio-cultural factors prevent women from undergoing gynecological inspection, which results in a higher risk of mortality from cervical cancer in certain population groups as indigenous communities. This study aimed to compare the concordance in HPV detection from urine and cervical samples, to propose an alternative to cervical scraping, which is commonly used in the cervical cancer screening. Methodology The DNA from cervical scrapings and urine samples was extracted using the proteinase K method followed by precipitation with alcohol, phenol andchloroform; a modification of the proteinase K method was developed in the management of urine sediment. Viral genotyping was performed using INNOLipa. Results The study population consisted of 108 patients from an indigenous population at southern Mexico, 32 without squamous intraepithelial lesions (NSIL) and 76 with low squamous intraepithelial lesions (LSIL). The majority of NSIL cervical scrapes were negative for HPV (90.63%), whereas more than half of LSIL cases were high-risk HPV positive (51.32%), followed by multiple infection by HR-HPV (17.11%), and multiple infection by LR- and HR-HPV (9.21%). No statistically significant relationship between the cytological diagnosis and the HPV genotypes detected in the urine samples was observed. A concordance of 68.27% for HPV positivity from urine and cervical samples was observed. Similarly, a concordance of 64.52% was observed in the grouping of HPVs by oncogenic risk. HR-HPV was detected in 71% of the urine samples from women with LSIL diagnosis, which suggests that HR-HPV detected in a urine sample could indicate the presence or risk of developing SIL. Conclusion HR-HPV detection in urine samples could be an initial approach for women at risk of developing LSIL and who, for cultural reasons, refuse to undergo a gynecological inspection.
Keywords: HPV; Cervical cancer; Urine; Cervical scraping; HPV screening; Indigenous population